Revealing optical vortices with a small number of photons (Laser Photonics Rev. 11(1)/2017). Issue 1 (January 2017) - Zhang, Wuhong; Wang, Jikang; Li, Fangshu; Chen, Lixiang; Karimi, Ebrahim
Abstract : The optical vortices embedded in a light field scattered by an object may contain abundant information from the object. However, their identification becomes very challenging when the detected light field is ultra‐weak. Based on the development of spiral phase filtering technique with high‐order vortex phase plates, the researchers from China and Canada present a high‐efficiency scheme to illuminate these vortices with only a small number of photons. In their demonstration, both the topological charge and location of each hidden vortex can be well visualized then revealed by a bright focused spot after scanning the high‐order vortex phase plates. This easy‐to‐implement filtering technique might be integrated into telescopes to detect optical vortices of weak signals from distant astronomical objects. (Picture: Wuhong Zhang et al., article number 1600163, in this issue)